2022
DOI: 10.1002/jper.21-0591
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the periodontal phenotype in premolar and molar sites on bone loss following full‐thickness mucoperiosteal flap: A 1‐year prospective clinical trial

Abstract: Background: Full-thickness mucoperiosteal flap (FTF) elevation could potentially affect the periodontium of the involved teeth; it is not clear if the periodontal phenotype of teeth involved in a FTF may influence these changes. The aim of this study was to evaluate the impact of FTF on teeth periodontium, as well as assessing the impact of periodontal phenotype on bone remodeling. Methods: In this single arm prospective clinical trial, 26 subjects and a total of 52 adjacent teeth were included. Patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…In different animal studies, authors have demonstrated that the elevation of either full- or split-thickness flaps induces osteoclast activity that causes subsequent bone resorption [ 36 41 ]. Similar vertical and horizontal bone loss was observed by Saleh et al [ 42 ] after full-thickness flap elevation during implant placement. In the case of horizontal GBR, similar bone resorption has not previously been described.…”
Section: Discussionsupporting
confidence: 85%
“…In different animal studies, authors have demonstrated that the elevation of either full- or split-thickness flaps induces osteoclast activity that causes subsequent bone resorption [ 36 41 ]. Similar vertical and horizontal bone loss was observed by Saleh et al [ 42 ] after full-thickness flap elevation during implant placement. In the case of horizontal GBR, similar bone resorption has not previously been described.…”
Section: Discussionsupporting
confidence: 85%
“…Both baseline and final STL‐DICOM files were imported to a software package (Romexis, Planmeca v.5.2.1., Hoffman Estates, IL, USA) and superimposed by matching at least eight points using bone landmarks to allow the visualization of soft and hard tissue structures beneath the overlying surface, as described elsewhere (Couso‐Queiruga, Tattan, et al, 2021 ; Saleh et al, 2022 ). At baseline, a sagittal section was made in the middle of each tooth of interest.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 The bone phenotype has been recognized as a key prognostic factor in periodontics and implant dentistry, particularly in the context of tooth replacement therapy after tooth extraction. [9][10][11][12][13][14] However, other periodontal phenotypic features related to the vertical dimension of the supracrestal soft tissue deserve specific attention.…”
Section: Introductionmentioning
confidence: 99%